Business Development Strategy of Lumindai Palm Sugar Home Industry with BMC and SWOT Approach - Zain, Elvita Putri; Azrifirwan; Permata, Deivy Andhika (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study aims to analyze and develop a business strategy of the lumindai palm sugar industry in Sawahlunto City, Indonesia by combining BMC and SWOT approaches. To identify the industry, a BMC mapping is initially performed. The results from the BMC serve as inputs for categorizing business development elements. These elements are then divided into four SWOT categories: Strengths, Weaknesses, Opportunities, and Threats. Each factor within these categories is evaluated and assigned a value, followed by an analysis using IFE and EFE. The IFE analysis yields a score of 3.045, indicating strong internal capital for industry development. Conversely, the EFE score of 2.636 suggests that the industry's external conditions are moderate. The IFE and EFE results then serve as a basis for formulating relevant strategies using the IE matrix. According to the IE matrix, the industry falls into cell IV, placing it in the Grow and Build position. This position is used to develop detailed strategic specifications in the SWOT matrix, which provides actionable insights for industry growth.